The biopsychosocial processes in autism spectrum disorder - Silva, Edgar Bittner; Filipini, Rosangela; Monteiro, Carlos B; Valenti, Vitor Engrácia [UNESP]; Carvalho, Sionara Melo Figueiredo de; Wajnsztejn, Rubens; Abreu, Luiz Carlos de (My University, 2013)
Background: Autism is a disorder characterized by pervasive social and communicative impairments, repetitive and stereotyped behaviors and restricted interests. Its causes and effects have been researched from various neurocognitive theoretical perspectives and with the aid of neuroimaging technology. We aimed to describe biopsychosocial processes characteristic of the Autism Spectrum Disorders. Method: Literature review using Medline and Scopus databases published between 2001 and 2011, with the keywords "autism", "theory of mind", "executive functions", "central coherence" and “fMRI”. Results: The studies found were plotted and organized into tables and an explanatory diagram of the main findings was produced. Conclusions: The most popular neurocognitive theories are still unable to fully explain the characteristics of the complications that autistic spectrum disorder causes to the quality of life of individuals living with autism. The association of clinical research and neuroimaging may contribute to a better understanding of the functioning of the brain affected by the disorder.